A numerical study of slug bubble growth during flow boiling in a diverging microchannel. (2nd October 2021) - Lin, Yuhao; Luo, Yang; Li, Wei; Sokolova, Ekaterina; Cao, Yanlong; Minkowycz, Wally J.
Abstract: The diverging microchannel has a gradually expanding cross-section area along the flow direction that can reduce flow instability and hence partial dry out. Utilizing the VOF method, Hardt and Wondra phase change model, and dynamic refined mesh scheme within a self-developed OpenFOAM solver, the vapor slug bubble's growth inside diverging and uniform microchannels are investigated. The effects of mass flux, heat flux, and diverging gradient on the bubble behavior and flow instability are discussed. The bubble growth caused the upstream flow to slow down and downstream flow to speed up, which lead to the pressure drop oscillation. The velocity of the flow is higher in the diverging microchannel cases, either upstream or downstream the vapor slug bubble. These indicate the expanding cross-section area can promote the bubble to move toward the downstream outlet thus mitigate the blockage of the channel and flow instability. HIGHLIGHT: The effects of slug bubble growth on flow and heat transfer are revealed through numerical investigation. The bubble growth process varied in the diverging and uniform microchannels. The diverging channel can help mitigate the blockage of the microchannel and flow instability.